(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2022)
The main aim of this article is to explore the pragmatic information contained in bilingual Italian-Spanish dictionaries, through the analysis of some linguistic elements. Since pragmatics is the study of the word in a context, we will focus on sentece formulas, which represent perhaps the most complex and least defined set of phraseological units. Full of pragmatic meaning and deprived of textual autonomy, they are communicative units without which the language would be much less expressive. In the colloquial discourse they play a key role, but because of their spontaneity and their structural peculiarities, they are not always ascribable to fixed categories and they can result very difficult to be used from a foreign perspective.